Safety of Transmission in Railway Applications - Maria Franekova (Advances in Electrical and Electronic Engineering, 2003)
The paper deals with the problems of data security in safety - related transmission systems defined within railway process. It is intent on summary of treats and security tools against them within closed and open security systems. In details is analysed possibility of using channel coding techniques and cryptography mechanisms, which are defined according to norms EN 50159. For chosen security mechanisms are deal mathematical apparatus of probability of undetected error determination for channel decoders, relations for determination decipher encoder's complexity and error probability of cryptography code word.